The Enhanced Rights for Detained Persons: Application of the Remedy of Habeas Corpus under the Cameroon Criminal Procedure Code (Strathmore Law Journal, 2020)
The incorporation of habeas corpus and bail in the Cameroonian Criminal Procedure Code has not only entrenched them in law, but has also widened and deepened their scope, with a view to obtaining, as far as possible, the respect for human rights and the rule of law in order to ensure a more functional criminal justice system in Cameroon. The incorporation of habeas corpus and bail in the Cameroon criminal trial process will restrain the arbitrary and illegal use of the powers of the judicial police officers and ensure respect of human rights. Although there are some challenges in the application of habeas corpus and bail such as misuse of the remedies by some overzealous authorities, defiance of court orders in the enforcement of the writ of habeas corpus by administrative authorities, and erosion of confidence in the Judiciary, there is optimism in the conscious efforts being made to ensure that habeas corpus and bail are properly applied so that the Cameroonian Criminal Procedure Code attains its full potential.